Utilization of Legume Forages as Protein Supplements for Ruminants - Bodee, Khamseekhiew (2001)
An assessment of four legume forages, namely Leucaena hybrid-Bahru (Leucaena-Bahru), Leucaena hybrid-Rendang (Leucaena-Rendang), Gliricidia sepium (G. sepium) and Arachis pintoi (A. pintoi) as protein supplements for ruminants was conducted in four studies. In experiment 1, chemical composition and ruminal and intestinal digestibilities of the test materials were determined. Crude protein (CP) contents of the two Leucaena hybrids and G. sepium were over 20%, while that for A. pintoi was marginally lower. Tannin content of Leucaena hybrids (averaged of 7.9%) was significantly (p<0.05) higher than those of G. sepium (3.7%) and A. pintoi (2.0%). Ruminal and intestinal digestibilities of G. sepium and A. pintoi were significantly (p<0.05) higher than those of Leucaena hybrids, while digestibility differences between G. sepium and A. pintoi.were smaller. Total tract digestibility for G. sepium was the highest (85.6%), followed closely by A. pintoi (78.4%). The above values were significantly higher (p<0.05) than those of the two Leucaena hybrids (averaged 52.2%). In experiment 2, the effects of levels of legume supplementation on fibre digestion and rumen environment were examined. The results showed that increasing legume supplementations improved ruminal NH3N and VF A concentrations and DM digestion. The results of this experiment indicate 40% supplementation would provide on optimal level ofNH3N for microbial synthesis. In experiment 3, acceptability (palatability) of the three legumes was examined using the choice feeding technique in sheep. The sheep showed highest preference for Leucaena-Bahru, followed by A. pintoi and G. sepium, but intake of A. pintoi the highest, followed by Leucaena-Bahru and G. sepium.